A report on bats survey at Air Panas-Gua Musang, Kelantan, Malaysia - Hasan, Noor Haliza; Anwarali Khan, Faisal Ali; Senawi, Juliana; Ketol, Besar; Sait, Isa; Abdullah, M.T. (Journal of Tropical Biology & Conservation (JTBC), 2016)
A short survey was conducted during the Banjaran Titiwangsa (Titiwangsa Range) expedition organised by the Department of Wildlife and National Parks to assess bat species diversity.